Analysis of Soil Carbon Content Variation in Four Different Land Use Types in West Lombok - Baiq Dewi Alya Nilyana Putri; Lalu Arifin Aria Bakti; Zaenal Arifin; Muhammad Zaki (Journal of Biology, Environment, and Edu-Tourism, 2025)
Soil plays a vital role as a natural sink for atmospheric carbon emissions, contributing to climate change mitigation. This study aimed to analyze soil carbon content across four different land use types-conservation forest, mangrove forest, mixed garden, and paddy field-in West Lombok District, and to assess its relationship with soil physical properties. A descriptive survey method was employed, with soil sampling conducted at depths of 0–10 cm and 10–20 cm across 24 plots. Data were analyzed using ANOVA and correlation tests. The results revealed significant variation in soil carbon content among land use types, with conservation forest exhibiting the highest value (4,010 tons/ha), followed by paddy field (3,894 tons/ha), mixed garden (2,694 tons/ha), and mangrove forest (1,184 tons/ha). Soil bulk density (BV) showed a strong positive correlation with carbon content, while porosity was negatively correlated. These findings suggest that land use and soil structure significantly influence soil carbon storage. Conservation forests, with higher organic input and minimal disturbance, are the most effective in sequestering carbon. This study highlights the importance of sustainable land use planning in enhancing soil carbon sequestration as a climate mitigation strategy.